En Seiger fra Ålborg - Galster, Georg (Kuml, 1961)
A "Seiger" from Aalborg In the spring of 1961 excavations were made in the square in front of the Saint Budolphi cathedral in Aalborg, the ancient commercial town on the Liim Fiord in the northern part of Jutland. The earth that was dug up was removed to the garden of Mr. Paul H. Rasmussen, engineer, in the suburb of Vejgaard. Mr. Rasmussen is president of the Aalborg branch of the Jutland Archaeological Society, and during the spring members of this society, having sifted the heaps of earth in collaboration with the Historical Museum of Aalborg, found a great many interesting objects from the millenarian community. Among other things they found the object depicted in fig. 1, which has been most skilfully identified by the Aalborg archaeologists as being a "seiger". It is a coin-balance with which full weight coins and overweight coins could easily and quickly be picked out. Made of bronze, it is collapsible and adjusted for coins weighing about 1.3 grammes and over. A similar balance of unknown provenance lay for many years in the National Museum (fig. 2). In 1931 it was dealt with and its use explained in "Fra Nationalmuseets Arbejdsmark" (Yearbook, Danish National Museum). In this connection attention was drawn to a 13th century stained glass from the Cathedral of Le Mans, the capital of Maine, the former county in France. The ancient donor, the moneychanger Franco d’Alonnes, had had three pictures (fig. 3) painted of the activities in his shop. The first of these pictures has long been misinterpreted as a mint master stamping out coins on a machine (!), see the "Revue Numismatique" 1840, the great work on Norwegian mediaeval coins 1865 and even "Die Technik der Antike und des Mittelalters" 1931 by Feldhaus. Yet the correct interpretation had been given as early as in 1851 and again, in more detail, in 1864 by M. Hucher, curator of the museum in Le Mans whose interpretation has been reprinted in extenso above. Franco is unmistakably described as a money-changer (scambiator) and not as a mint master. The coins he is weighing may be from the county of Maine, but they are more likely to be gros tournois, the international trade coin introduced in 1266 by Louis IX the Saint. Franco’s business must have been entirely legal. Perhaps he had a connection with the mint of the neighbouring city of Tours. If persons other than mint masters (and money changers attached to the mint) picked out current coins on a "seiger" it was considered harmful to the community and they were punished with loss of life and properly in the same way as counterfeit coiners. Municipal laws were quoted from Freiberg, Erfurt (1329) and Augsburg (1498); German Coinage Acts were passed in 1385, 1551 and 1559 all to this effect. Nevertheless this illegal practice continued and culminated in the "Kipper-Wipper time" from 1619 to 1622. This was due to the rough-and-ready weighing and adjusting of coins al marco. Coins were not weighed one by one, but when, for instance, 240 pennies altogether weighed one mark the ordinances were complied with. It would then be a lucrative business for an acquisitive tradesman to pick out the heaviest coins and melt them down: the resulting debasement of the coinage was a serious blow to the lord of the mint and his subjects. The "seiger" from Aalborg was adjusted for coins weighing some 1.3 grammes, and this weight exactly fits the Hanseatic "witten"s which were struck in Lubeck, Hamburg, Wismar, and Lunenburg from 1340 onwards. These coins were current particularly in Denmark, and one may suppose that a coin balance was lost by a tradesman in Aalborg in the 14th century. As above mentioned by M. Hucher, similar balances have been in use in our own time too, thus the last picture (fig. 8) represents a gold coin balance from the National Bank of Denmark which was in use until 1931 when the Danish gold 10 and 20 kroner coins were withdrawn from circulation. In this case the purpose was to select the coins that had become too light through use and which were to be melted down. Georg Galster.